Combined glaucoma and cataract surgery: Comparison of viscocanalostomy, endocyclophotocoagulation, and ab interno trabeculectomy. Issue 5 (May 2018) - Moghimi, Sasan; Hamzeh, Nikoo; Mohammadi, Massood; Khatibi, Nassim; Bowd, Christopher; Weinreb, Robert N.
Abstract : Purpose : To compare outcomes of phacoemulsification combined with viscocanalostomy, endocyclophotocoagulation (ECP), or ab interno trabulectomy for intraocular pressure (IOP) control and safety in eyes with open‐angle glaucoma and visually significant cataract. Setting : Farabi Eye Hospital, Tehran, Iran. Design : Retrospective case series. Methods : Medical records of patients who had combined surgery and were followed for at least 1 year were reviewed. Complete success, postoperative IOP, number of medications at each visit, and complications were evaluated and compared before and after adjustments for confounders. Results : Forty‐six eyes had combined phacoviscocanalostomy, 35 had phaco–ECP, and 28 eyes phaco–ab interno trabulectomy. The groups were matched for baseline IOP ( P = .24). At the final follow‐up (mean 17.2 months ± 5.5 [SD]), the phacoviscocanalostomy group had the lowest mean IOP (13.5 ± 4.7 mm Hg, 29% decrease) ( P = .01). There was no significant difference in the final IOP between phaco–ECP and phaco–ab interno trabulectomy (16.4 ± 3.9 mm Hg, 20% decrease versus 15.8 ± 4.2 mm Hg, 15% decrease) ( P = .88). The reduction in the number of medications was greater with phacoviscocanalostomy (77%) than with phaco–ECP (40%) and phaco–ab interno trabulectomy (44%) ( P = .01). Phacoemulsification–ab interno trabulectomy had the fewest complications. Intraocular pressure spikes were more frequent in the phaco–ECP group (20%) than in the other groups (4%) ( P = .05). Conclusions : All procedures significantly lowered IOP. Phacoemulsification–ab interno trabulectomy resulted in fewest complications and phacoviscocanalostomy led to the largest IOP drop and largest reduction of medications.